State Fragility and Organized Crime - Thapa, Rabi Raj (Journal of APF Command and Staff College, 2019)
There are always probabilities of strong relationships between transnational organized crime group, the government, semi-government agencies and irregular formations. Because, at the fundamental level, motivations and aspirations of all these agencies and groups may be similar, i.e. making as much money or profit as quickly as possible; whether in a semi-legitimate or illegitimate means and ways. For this, they will be ready to use any modus operandi; the end result and harm they cause to the nation and society will be the same. Therefore, more often it is also very difficult to distinguish them one from another. In this regard, they all can be termed “the silent partners” of the legitimate government agencies, semi-government corporations and the organized crime groups (OCGs) and wherever they belong: they converge at a single platform, i.e. the Organized Crime. Therefore, the silent partners of the Organized Crime Group can be any of these: a private party or person, a government officer or his office, a semi-government official or a group of people belonging to these organizations. There may be another similarity among these too;…i.e. they all do their utmost to avoid their appearance in public or willingly acknowledged their involvement in any form and deeds on such cooperative undertaking. There are many ways such organized syndicates apply their methods that may be soft, peaceful to even gruesomely violent means to get access to state power, money or government resources. In this regard, they may apply all types of legitimate and illegitimate means, to name the few, such as protection rackets, and capture public resources, seize of property and land forcibly in an illegitimate way, and eventually entry into the licit private sector by money laundering and other means.